Cytotoxic Potential of Mangifera indica L var Arumanis Rind Extract and Fraction Against T47D Cells with Microtetrazolium (MTT) Method - Ifmaily, Ifmaily; Oktafera, Oktafera (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Breast cancer is a major problem in the health sector, one type of malignant cancer in Indonesia and the world. Medical therapy for cancer patients has had side effects such as nausea, vomiting, weakness, diarrhea and hair loss. The arumanis mango rind, in previous research, contains secondary metabolites of flavonoids, phenolics, saponins and tannins. Arumanis mango rind extract has been studied to have antioxidant activity with an IC50 of 18.29 µg/ml and a toxic, toxicity test with an LC50 of 169.04 µg /ml. The aim of the research was to determine the cytotoxic potential of arumanis mango rind extract and fractions against T47D cancer cells using the Microtetrazolium (MTT) method from the percentage of cancer cell viability, IC50, and cancer cell morphology. It was using ethanol extract, n-hexane fraction, ethyl acetate fraction, and n-butanol fraction, with concentrations of 1000, 100, 10, 1, 0.1 μg/ml against T47D cancer cells. Data were the life cell absorbance obtained from the ELISA reader, to calculate the percentage of T47D cell viability, obtain IC50, then observe the morphology of the cancer cells. The results of the percentages of cell viability ( μg/ml ) from the ethanol extract were 81.1: 103.5; 137.3; 163; 165.5, n-hexane fraction were 28.5; 82.7; 105.1; 130.5; 132.5, ethyl acetate fraction were 15.9; 27.2; 101.7; 134.1; 162.7, n-butanol fraction were 32.6; 75.6; 82.8; 122.3; 146.4, doxorubicin as a comparison were 22.6; 38.4; 45.4; 53.4; 56. The IC50 results of the ethanol extract, the n-hexane fraction, the ethyl acetate fraction, the n-butanol fraction, and doxoburicin were 32.21; 616.59; 90.57; 338.84, and 1.44. The best of cancer cell morphology was doxorubicin, ethanol extract, and ethyl acetate fraction. The conclusion that the extract and fraction of arumanis mango rind had cytotoxic potential against T47D cancer cells from the percentages of cell viability, IC50 and cancer cell morphology, and the best of result are ethanol extract, ethyl acetat fraction, also doxorubicin as comparison drug.